Training on the STEAM Learning Model to Improve the Competence of Elementary School Teachers - Muhammad Amran; Erma Suryani Sahabuddin; Usman Usman; Abdul Majid; Ainun Najib Al Fatih (Universitas Lambung Mangkurat, 2026)
This community service activity aims to improve the professional competence of elementary school teachers in Barru Regency in designing and implementing the Science, Technology, Engineering, Arts, and Mathematics (STEAM) learning model in Science subjects. Twenty-first-century learning requires teachers to integrate multiple disciplines to develop students’ critical, creative, collaborative, and communicative skills. However, in practice, elementary school teachers still face limitations in understanding and skills in implementing integrated STEAM-based learning. The implementation method for this community service uses a training and mentoring approach, including the socialization of STEAM concepts, workshops on developing STEAM-based science learning tools, teaching practice, and reflection and evaluation. The results of the activity indicate an improvement in teachers’ understanding of the STEAM concept and their ability to develop STEAM-based science learning tools. This activity is expected to contribute to improving the quality of science learning in elementary schools.